Chiral recognition ability of amylose derivatives bearing regioselectively different carbamate pendants at 2, 3- and 6-positions. (15th August 2019) - Dai, Xiao; Bi, Wanying; Sun, Mengchen; Wang, Fan; Shen, Jun; Okamoto, Yoshio
Highlights: Synthesis and chiral recognition of novel amylose derivatives. Novel amylose derivatives with regioselective substituent at 2, 3- and 6-positions. Regioselective protection at 2, 3-positions using bulky trimethylphenyl group. Racemic compounds better resolved on the obtained CSPs than Chiralpak AD. Chiral recognition delicately depends on the substituents. Abstract: Seven amylose derivatives bearing two regioselective carbamate pendants at 2, 3- and 6-positions of a glucose unit were synthesized through protection and deprotection at the 6-position. The chiral recognition abilities of the obtained derivatives were evaluated as the chiral stationary phases (CSPs) for high-performance liquid chromatography (HPLC). Each derivative had its own characteristic recognition ability depending on the arrangement of carbamate pendants at the three positions. The nature, position and number of the substituents on the aromatic moieties of pendants play a significant role on the chiral recognition ability of these derivatives. Most amylose derivatives exhibit good enantioselectivity for the racemates in this study, and those bearing electron-withdrawing para -chlorophenylcarbamates at 2- and 3-positions possessed relatively better chiral recognition than others. Some racemates could be better resolved on the amylose derivatives with different pendants than on Chiralpak AD, one of the most powerful commercially available chiral columns derived from amylose tris(3, 5-dimethylphenylcarbamate).